2022
DOI: 10.1111/jfpp.16792
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of tigernut ( Cyperus esculentus ) tuber starch and its application in steamed bread

Abstract: Tigernut (Cyperus esculentus L.), native to northeast Africa, belongs to the sedge family (Babiker et al., 2021). It is an important multipurpose crop, its stems and leaves can be used as green feed and knitting materials, and the roots with a fragrant smell are a potential source of essential oils (Duman, 2019;Lasekan, 2013;Ozcan et al., 2021). Tigernut tubers are rich in lipids, proteins, starches, dietary fibers, and vitamins, which are usually applied to develop edible oil, plant milk, and snack food (Clem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…NTS had the sharp diffraction peaks of NTS at 15°, 17° and 23°, which did not changed significantly in the XRD spectrum of CLTS, indicating that the cross-linking reaction did not change the crystal type of NTS, and it was still C-type starch. Our results was consistent with the previous report (Lv et al, 2022). However, the crystallinity of CLTS (12.4%) was higher than that of NTS (11.3%).…”
Section: Xrd Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…NTS had the sharp diffraction peaks of NTS at 15°, 17° and 23°, which did not changed significantly in the XRD spectrum of CLTS, indicating that the cross-linking reaction did not change the crystal type of NTS, and it was still C-type starch. Our results was consistent with the previous report (Lv et al, 2022). However, the crystallinity of CLTS (12.4%) was higher than that of NTS (11.3%).…”
Section: Xrd Analysissupporting
confidence: 93%
“…As a kind of multi-purpose crop with high comprehensive utilization value, tigernut has more comprehensive nutrients than wheat and corn, and its starch content is as high as 26%-30% (Liu et al, 2019). Previous studies have found that tigernut starch has good gel properties, and it belongs to slow digestion starch, which can be used in functional foods to reduce postprandial blood glucose (Lv et al, 2022;Wang et al, 2022). However, like other natural starches, tigernut starch also has some inherent defects and needs to be modified.…”
Section: Introductionmentioning
confidence: 99%
“…The freeze–thaw stability of the composite flours was determined with reference to the procedure documented by Lv et al . (2022). An aqueous solution of each composite flour (6% dry basis) was heated in a water bath at 100 °C for 30 min until completely gelatinized.…”
Section: Methodsmentioning
confidence: 99%
“…The amylose contents of NAS and HAS were determined using the colorimetric method ( Lv, Zhang, Zhen, Shi, & Liu, 2022 ). First, 2.5 mL of 1 mg/mL standard solution with different amylose and amylopectin ratios was mixed with 20 mL of distilled water, and its pH was adjusted to 3.0.…”
Section: Methodsmentioning
confidence: 99%